Isolation and identification of indigenous biosurfactants producing bacteria from motor oil / Ang Chung Huap, Cindy Tan Soo Yun and Millaa-Armilla Asli - Ang, Chung Huap; Cindy Tan Soo Yun; Millaa-Armilla Asli (Research Management Institute (RMI), 2012)
A biosurfactant is a type of complex bio-based material that is produced by microorganisms which have the ability to lower the surface and interfacial tensions of liquids. Being amphiphilic molecules, the polar moiety (hydrophilic) consists of carbohydrate, amino acid or phosphate group. Meanwhile, the hydrophobic (nonpolar) parts are usually long carbon chains and fatty acids. They accumulate between fluid phases, can form micelles and thereby enhance the solubility of poorly soluble compounds in water. Various microbial surfactants have been successfully produced using different types of water soluble and insoluble carbon sources including crude petroleum and motor lubrication oils. This study aims to screen and identify indigenous bacterial strains isolated from motor oil contaminated soil samples which are capable of synthesizing microbial surfactants. Motor oils consist of aliphatic and aromatic hydrocarbons such as naphthalene, benz(a)anthracene, benzo(a)pyrene, and fluoranthene. Furthermore, used motor oils also contain heavy metals such as zinc, magnesium, barium, lead, aluminium, chromium, copper, iron, nikel, silicon, and tin. All these elements can cause severe environmental pollutions when used motor oils leaks onto earth surface. The biosurfactants producing bacteria will be identified using standard morphological method and DNA sequencing method. DNA sequencing of bacterial 16S rRNA region amplified by universal primers will provide an accurate identification result within shorter time. In addition, biosurfactants produced by the indigenous bacteria will also be tested for additional potential usages such as surface tension reduction and antimicrobial properties. The biosurfactants are favoured than chemical surfactants owing to their low toxicity, biodegradability, mild production conditions that use cheap waste substrates and are versatile at extreme salinity, temperature and pH. Major applications of biosurfactants include enhanced oil recovery, degradation of hydrocarbons and removal of pesticides as well as in the healthcare and food processing industries.